ADAPTATION OF THE MAPLE SYSTEM FOR EFFECTIVE STUDENT'S INDEPENDENT WORK IN HIGH MATHEMATICS - Krupskyi, Yaroslaw; Tuituinnyk, Oksana; Yashchuk, Olesya; Klieopa, Іrina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The significance of the material presented in the article is due to the necessity of developing and implementing the latest information technologies at the study of higher mathematics using the systems of computer mathematics. The solution of the standard tasks of higher mathematics on the topic of differential equations involves the execution of bulky, similar arithmetic calculations and records. If there is an error in the calculation, its localization takes a lot of time, which leads to the student's quick fatigue. The concept of adaptation of SCM Maple to higher mathematics is suggested by creating a training Maple simulator on the topic "Linear homogeneous differential equations" in order to more effectively master students 'material, as well as to enhance students' learning and cognitive activity. The main results of the authors are presented in the field of development of the educational complex in higher mathematics, the main element of which are procedural simulators as well as procedure generators.